E-Proc como ferramenta de accountability judicial comportamental - Araújo, Rodrigo da Silva Perez (Universidade Federal do Tocantins, 2019)
Propositive dissertation that aimed to demonstrate the importance of active transparency of the Judiciary and the balance of the equation judicial independence versus judicial behavioral accountability of its members in the context of the justice system, understood as a network in which communication is the central element of its conformation and development. The study is justified by the relevance of the matter for the improvement of the service rendered by justice to society, which perceives it as time consuming and of low effectiveness. The quantitative-qualitative method was the most adequate to the proposed objectives of knowing the degree of accomplishment of the duty of transparency carried out by the Judiciary. The data collection was done through reports of procedural movement of the e-PROC system related to the years of 2015, 2016 and 2017, and data provided by the Parametrization Commission of the Strategic Management Coordination of the Judiciary of the State of Tocantins, as well as administrative demands from the Presidency of the Court and requested by this department. In addition, extensive bibliographical material was used, which was done through consultations with books, scientific articles, legislation and Internet pages. The results indicate the need to expand the initiatives related to the free flow of information in the justice network, in relation with high education institutions and, specifically, to determine the elaboration of an action plan for the adoption of public policy of open data, as it would advance towards the opening of the Judiciary.